2002
DOI: 10.1080/10640260290081849
|View full text |Cite
|
Sign up to set email alerts
|

Self-Harm and Bulimia Nervosa: A Complex Connection

Abstract: There is some evidence to suggest that eating disordered individuals are unusually likely to engage in self-harm behavior. However, the nature of the relationship among self-harm, bulimia nervosa, and related constructs such as borderline personality disorder and multi-impulsive bulimia nervosa remains unclear. This article briefly addresses the nature of this relationship and discusses two possible mechanisms for self-harm behavior in bulimia nervosa. Additionally, a protocol for managing such behavior in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
5
1
1
Order By: Relevance
“…Two lines of distinct but overlapping research have examined this issue, one involving a highly impulsive subgroup of bulimics called "multi-impulsive bulimics" and the other exploring the role of comorbid borderline personality as a potential mediator or contributor to sexual promiscuity in women with BN (Wonderlich, Myers, Norton, & Crosby, 2002). Two lines of distinct but overlapping research have examined this issue, one involving a highly impulsive subgroup of bulimics called "multi-impulsive bulimics" and the other exploring the role of comorbid borderline personality as a potential mediator or contributor to sexual promiscuity in women with BN (Wonderlich, Myers, Norton, & Crosby, 2002).…”
Section: Hypersexual Behavior (Sexual Promiscuity)mentioning
confidence: 99%
“…Two lines of distinct but overlapping research have examined this issue, one involving a highly impulsive subgroup of bulimics called "multi-impulsive bulimics" and the other exploring the role of comorbid borderline personality as a potential mediator or contributor to sexual promiscuity in women with BN (Wonderlich, Myers, Norton, & Crosby, 2002). Two lines of distinct but overlapping research have examined this issue, one involving a highly impulsive subgroup of bulimics called "multi-impulsive bulimics" and the other exploring the role of comorbid borderline personality as a potential mediator or contributor to sexual promiscuity in women with BN (Wonderlich, Myers, Norton, & Crosby, 2002).…”
Section: Hypersexual Behavior (Sexual Promiscuity)mentioning
confidence: 99%
“…Given the presence of a personality disorder, will empirically confirmed interventions for eating disorders such as cognitive behavioral therapy really be successful in the absence of a reparative and psychologically intimate therapeutic relationship? Are other types of relationally-based treatments indicated, such as Interpersonal Therapy (Fairburn, 1997), psychodynamic therapy (Sansone & Johnson, 1995;Dennis & Sansone, 1997), or Integrative Cognitive Therapy (Wonderlich, Myers, Norton, & Crosby, 2002)? For specific types of personality disorders, should treatment necessarily be augmented with particular intervention strategies (e.g., Dialectical Behavior Therapy and borderline personality disorder; Linehan, 1993), and do these general techniques require modification when integrated into the treatment of eating disordered individuals?…”
mentioning
confidence: 98%
“…Prevalence rates among non-clinical samples of adolescents and young adults range from 4% (Klonsky & Muehlenkamp, 2007) to 38% (Whitlock, Eckenrode, & Silverman, 2006; Lloyd-Richardson et al 2007), whereas prevalence rates among inpatient adolescents have been reported at 30 to 68% (Makikyro et al, 2004; Nixon, Cloutier, & Aggarwal, 2002). Of particular interest are findings that rates of NSSI tend to be quite high among a subset of persons with select psychiatric disorders including borderline personality disorder (Zanarini, Frankenburg, Ridolfi, & Jager-Hyman, 2006), and eating disorders; especially bulimia nervosa (BN; Anderson, Carter, & McIntosh, 2002; Claes, Vandereycken, & Vertommen, 2001; Favaro & Santonastaso, 1999; Wonderlich, Myers, Norton, & Crosby, 2002). …”
mentioning
confidence: 99%